Metyrapone Versus Osilodrostat in the Short-Term Therapy of Endogenous Cushing’s Syndrome: Results From a Single Center Cohort Study - Detomas, Mario; Altieri, Barbara; Deutschbein, Timo; Fassnacht, Martin; Dischinger, Ulrich (Frontiers in Endocrinology, 2022)
Background. Although surgery is considered the first-line treatment for patients with endogenous Cushing’s syndrome (CS), medical therapy is often required to control severe hypercortisolism. Metyrapone and osilodrostat are both steroidogenic inhibitors targeting the 11β-hydroxylase, however, their therapeutic effectiveness has not yet been directly compared. This study aimed to evaluate metyrapone and osilodrostat in the short-term therapy of CS. Methods. Retrospective analysis of patients with endogenous CS treated with metyrapone or osilodrostat as monotherapy for at least 4 weeks. Main outcome measures were serum cortisol and 24h urinary free cortisol (UFC) at baseline (T0) and after 2 (T1), 4 (T2), and 12 weeks (T3) of therapy. Results. 16 patients with endogenous CS were identified (pituitary n=7, adrenal n=4, ectopic CS n=5). Each 8 patients each were treated with metyrapone and osilodrostat. Despite heterogeneity, both groups showed comparable mean UFC levels at T0 (metyrapone: 757.8 µg/24h vs osilodrostat: 816.9 µg/24h; p=0.93). From T0 to T1, the decrease of UFC was less pronounced under metyrapone than osilodrostat (-21.3% vs -68.4%; median daily drug dose: 1000 mg vs 4 mg). This tendency persisted at T2 (-37.3% vs -50.1%; median drug dose: 1250 mg vs 6 mg) while at T3 a decrease in UFC from T0 was more pronounced in the metyrapone group (-71.5% vs -51.5%; median dose 1250 mg vs 7mg).Under osilodrostat, a QTc-interval prolongation was identified at T3 ( 432.5 ms vs 455.3 ms). From T0 to T2, the number of antihypertensive drugs remained comparable under metyrapone and decreased under osilodrostat (n= -0.3 vs n= -1.0). Conclusion. Although both drugs show comparable therapeutic efficacy, osilodrostat seems to reduce cortisol levels and to control blood pressure faster.